2020
DOI: 10.51406/jnset.v18i1.2040
|View full text |Cite
|
Sign up to set email alerts
|

Annona Muricata Linn. Ethanolic Leaf Extract Ameliorates Reproductive Complications in Streptozotocin-Induced Diabetic Wistar Rats

Abstract: Diabetes mellitus is an endocrine and metabolic disorder of humans and animals characterized by hyperglycemia and low blood insulin levels or insensitivity of target organs to insulin and it’s a major health problem affecting patient’s quality of life due to its many complications. Infertility is one of the major secondary complications in diabetes. Although numerous drugs have been used for intervention studies on diabetes-induced infertility worldwide, there are currently no treatments for diabetes associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…The mechanism of action linked to ELAM improved sperm count is flavonoids and saponins, which tend to repair tissue proteins and combat ROS formation in the testicular plasma membrane. The study has accordance with the reports of the study (65,66,68,78,79), revealing improved sperm count in testicular insult following Annona muricata extract, but contradict the findings of Oladipo et al (80) indicating significantly lowered levels of total sperm count following Annona muricata bark extracts. However, MET treatment significantly improved total sperm count, which is linked to the decline in oxidative stress and lipid peroxidation, enhancement of 5'-AMP-activated protein kinase activity, and restoration to the expected levels of pituitary-gonadal hormones (28).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mechanism of action linked to ELAM improved sperm count is flavonoids and saponins, which tend to repair tissue proteins and combat ROS formation in the testicular plasma membrane. The study has accordance with the reports of the study (65,66,68,78,79), revealing improved sperm count in testicular insult following Annona muricata extract, but contradict the findings of Oladipo et al (80) indicating significantly lowered levels of total sperm count following Annona muricata bark extracts. However, MET treatment significantly improved total sperm count, which is linked to the decline in oxidative stress and lipid peroxidation, enhancement of 5'-AMP-activated protein kinase activity, and restoration to the expected levels of pituitary-gonadal hormones (28).…”
Section: Discussionsupporting
confidence: 86%
“…Also revealed in the study is the attenuated effects of MET and ELAM in the ameliorative phase as indicated in groups C and D. The attenuated effect of MET is attributed to its ability to combat lipid peroxidation in the testicular membrane and its tissues as well, and the physiological mechanism of action by ELAM revealing a significant increase in active sperm motility and decrease in non-motile sperm levels is attributed to the presence of flavonoids and saponins, which combats redox formation by arsenic trioxide in the testicular tissue and spermatogenic process. Reports showed that Annona muricata improves sperm motility and non-motile sperm in testicular dysfunction caused by toxins, which supports the study's findings (65)(66)(67)(68)(69). However, MET administration showed improvement in sperm motility following testicular dysfunction in infertile studies (70)(71)(72)(73), which is in line with the study's outcome.…”
Section: Discussionsupporting
confidence: 85%